International perspectives on mathematics teacher education - Thompson, Denisse R. 1954-; Suurtamm, Christine, 1949-; Huntley, Mary Ann (Research in mathematics education series., 2021)
"Mathematics teacher education includes the mathematics content teachers need to understand, the ways that pedagogical approaches are developed, the messages about the nature of mathematics teaching and learning, and the interface between tertiary preparation and school contexts. Scholars from Sweden, France, Malawi, Singapore, New Zealand, Brazil, the USA, and Canada provide insights for the mathematics education community's understanding of how teacher educators in different countries structure, develop, and implement their respective mathematics teacher education programs. Several themes emerged across the chapters including: varied approaches to developing culturally responsive pedagogies and/or Indigenous perspectives to ensure equity and diversity for all students; issues and challenges in fostering partnerships and collaborations among various stakeholders, with partnerships involving connections with mathematics classroom teachers, school districts, and/or mathematicians or mathematics departments; strategies for developing mathematics knowledge for teaching, providing insights into messages about what it means to learn mathematics in terms of content and pedagogy; and preparing teachers who have flexibility and resourcefulness. This book will be of interest to those responsible for higher education, including teacher educators, researchers in mathematics teacher education, instructors of graduate courses preparing future teacher educators, as well as policy makers"--